Effect of Intravenous Dexamethasone in Combination with Caudal Analgesia on Post Operative Pain Control after Herniotomy in Children - Islam, Md Jahirul; Jahan, Ismat; Islam, Aminul (Dhaka Shishu (Children) Hospital Journal, 2020)
Background: Dexamethasone has a powerful anti-inflammatory action and has demonstrated reduced morbidity after surgery. Objectives: The aim of this study was to examine the effects of a single i.v. dose of dexamethasone in combination with caudalblock on postoperative analgesia in children. Methods: This study was a randomized, double blind clinical trial, in which 77 children of ASA I and II, aged 3-10 years, undergoing elective unilateral herniotomy operation, was allocated in a double blind manner. Control Group I consist of 39 patients and Dexamethasone Group II consists of 38 patients. Group II received i.v. Dexamethasone 0.5 mg/Kg (Maximum 20 mg) and Group I received the same volume of i.v. saline after induction of anaesthesia. After inhalation induction of general anaesthesia, children received either dexamethasone 0.5-1 mg/Kg (maximum 20 mg) (n=39) or the same volume of saline (n=38) i.v. A caudal anaesthetic block was then performed using 1.5 ml/kg of Bupivacaine 0.25% in all patients. After surgery, rescue analgesic consumption, pain scores, and adverse effects were evaluated for 24 h. Results: Significantly, fewer patients in the dexamethasone group required fentanyl for rescue analgesia (7.9% vs38.5%, p<0.05) in the post-anaesthetic care unit or acetaminophen (23.7% vs 64.1%) after discharge compared with the control group. The time to first administration of oral acetaminophen was significantly longer in the dexamethasone group (646 vs 430 min). Postoperative pain scores were lower in the dexamethasone group and the incidence of adverse effects was similar in both groups. Conclusion: Intravenous dexamethasone 0.5-1 mg/Kg in combination with a caudal block augmented the intensity and duration of postoperative analgesia with out adverse effects in children undergoing herniotomy. DS (Child) H J 2019; 35(2) : 145-149